Yaʿqūb b. al-Rabīʿ Read by al-Mutanabbī and al-Mubarrad: A Contribution to an Abbasid History of Emotions - Bray, Julia (Journal of Abbasid Studies, 2017)
The now little-known early Abbasid poet Yaʿqūb b. al-Rabīʿwas famous for his elegies on his slave woman, Mulk. While scholars such as al-Mubarrad transmitted them, along with a biography patterned on the “sold slave-girl” tale-type, al-Mutanabbī plagiarised them and reversed their message. This yields a corpus which can contribute to an Abbasid history of emotions. Approaches to the history of emotions are discussed in an introduction, and key elements of the corpus are translated in Appendices i to iii.